Cronenberg pedagogy and fleshy possibilities for educational futures. Issue 5 (2nd June 2023) - Sojot, Amy N
Instead of seeking the slick aesthetics of consumer-friendly creative stories, this paper ventures to the sublime of the incomprehensible and invites us to look into the abyss of education's possibilities. Drawing inspiration from Jeff Vandermeer's 2017 novel, Borne, and filmmaker David Cronenberg's aesthetic, this paper aims to tell a story that unfetters easily compartmentalized notions of creativity in education. Borne tells the story of a young female scavenger who finds and proceeds to care for a sentient—and quite vocally curious—experimental biotech remain, while Cronenberg's films famously bridge science fiction and body horror. Popular culture, in identifying this aesthetic, developed the slang term "to Cronenberg, " meaning to affectively highlight exaggerated mutations. To this end, this paper explores specific questions for educational futures: what does creativity mean for a Cronenberg pedagogy and how does the ethics of creativity inform future educational policy directions?